ANALISIS FAKTOR HUBUNGAN YODIUM DAN VITAMIN D TERHADAP KEJADIAN STUNTING PADA BALITA USIA 12-24 BULAN - Silaban, Titin Dewi Sartika; Salsabila, Salsabila; Riona, Septi (JOURNAL OF HEALTH SCIENCE, 2021)
Stunting or shortness is a condition of failure to grow and develop in infants (0-11 months) and toddlers (12-59 months) caused by chronic malnutrition, especially in the first thousand days of life, so that children are too short for growth. age. Malnutrition occurs since the baby is in the womb and in the early days after the baby is born, but stunting conditions only appear after the child is two years old. The purpose of the study: to determine the relationship between iodine intake and vitamin D intake with the incidence of stunting. This research is a quantitative research with an analytical survey with a cross sectional approach. The population in this study were all mothers who had toddlers aged 12-24 months. The sample of this research used simple random sampling method. The sample of this study amounted to 68 respondents. Data analysis was carried out in two stages, namely univariate analysis and bivariate analysis with Chi-square statistical test. The results of the bivariate analysis showed that there was a relationship between iodine intake (p value = 0.018), there was a relationship between vitamin D (p value = 0.000) and the incidence of stunting in children aged 12-24 months. These suggestions are expected to be taken into consideration in decision making, can improve the quality of services, especially regarding the incidence of stunting in toddlers aged 12-24 months. Keywords: Iodine, Vitamin D, Stunting Toddler 12-24 months